2014
DOI: 10.1620/tjem.233.283
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Lung Myofibroblasts Reveals the Anti-Fibrotic Effects of Cyclosporine

Abstract: Cyclosporine, a calcineurin inhibitor, is a potent immunosuppressive agent that acts chiefly through the inactivation of T-lymphocytes. Several clinical studies have demonstrated the effectiveness of cyclosporine for treating fibrotic lung disease, but the underlying mechanism remains elusive. We hypothesized that cyclosporine exerts direct effects against fibrogenesis of lung myofibroblasts, and aimed to elucidate the mechanism of this anti-fibrotic effect through gene-expression profiling using DNA microarra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Besides TGF-β, there has been recently a growing interest for the axis IGFs/IGFBPs in fibrosing process. A recently published study has shown a link between the production of TGF-β and the production of insulin-like growth factor binding protein-2 (IGFBP-2) [ 10 ] known to be related to IPF [ 11 ] within myofibroblasts cells derived from the lung. Moreover, IGFBP-2 was found at significantly higher level in the bronchoalveolar lavage of children with interstitial lung disease [ 12 ] relative to healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Besides TGF-β, there has been recently a growing interest for the axis IGFs/IGFBPs in fibrosing process. A recently published study has shown a link between the production of TGF-β and the production of insulin-like growth factor binding protein-2 (IGFBP-2) [ 10 ] known to be related to IPF [ 11 ] within myofibroblasts cells derived from the lung. Moreover, IGFBP-2 was found at significantly higher level in the bronchoalveolar lavage of children with interstitial lung disease [ 12 ] relative to healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclosporine A, an immunomodulatory drug, has been shown to increase TGF-β, α-SMA, and type I collagen expression in fibroblasts from some tissues (119,120), although in other tissue types it has inhibitory effects (121,122). Interestingly, cyclosporine A has recently been shown to reduce experimental myopia progression, although whether this was effected through changes in α-SMA expression was not investigated (123).…”
Section: Fibroblasts Myofibroblasts and Tgf-βmentioning
confidence: 99%
“…Hirota et al reported that CSA down-regulates the expression of a variety of genes that are increased by TGF-b, a fibrogenic cytokine, in lung myofibroblasts. 80 Furthermore, excessive TGF-b activity may lead to increased ocular surface inflammation, neovascularization, and cicatrization. 80,81 De Rojas et al described the use of cyclosporine either as monotherapy or in combination with another IMT in five patients with chronic ocular SJS/TEN.…”
Section: Calcineurin Inhibitorsmentioning
confidence: 99%
“…80 Furthermore, excessive TGF-b activity may lead to increased ocular surface inflammation, neovascularization, and cicatrization. 80,81 De Rojas et al described the use of cyclosporine either as monotherapy or in combination with another IMT in five patients with chronic ocular SJS/TEN. 1 Of note, OCP patients tend to respond poorly to calcineurin inhibitors; in one study, 490% failed this therapy.…”
Section: Calcineurin Inhibitorsmentioning
confidence: 99%